Oxidation of Protein Kinase A Regulatory Subunit PKARIα Protects Against Myocardial Ischemia-Reperfusion Injury by Inhibiting Lysosomal-Triggered Calcium Release. Issue 5 (2nd February 2021) - Simon, Jillian N.; Vrellaku, Besarte; Monterisi, Stefania; Chu, Sandy M.; Rawlings, Nadiia; Lomas, Oliver; Marchal, Gerard A.; Waithe, Dominic; Syeda, Fahima; Gajendragadkar, Parag R.; Jayaram, Raja; Sayeed, Rana; et al.
Abstract : Background: Kinase oxidation is a critical signaling mechanism through which changes in the intracellular redox state alter cardiac function. In the myocardium, PKARIα (type-1 protein kinase A) can be reversibly oxidized, forming interprotein disulfide bonds in the holoenzyme complex. However, the effect of PKARIα disulfide formation on downstream signaling in the heart, particularly under states of oxidative stress such as ischemia and reperfusion (I/R), remains unexplored. Methods: Atrial tissue obtained from patients before and after cardiopulmonary bypass and reperfusion and left ventricular (LV) tissue from mice subjected to I/R or sham surgery were used to assess PKARIα disulfide formation by immunoblot. To determine the effect of disulfide formation on PKARIα catalytic activity and subcellular localization, live-cell fluorescence imaging and stimulated emission depletion super-resolution microscopy were performed in prkar1 knock-out mouse embryonic fibroblasts, neonatal myocytes, or adult LV myocytes isolated from "redox dead" (Cys17Ser) PKARIα knock-in mice and their wild-type littermates. Comparison of intracellular calcium dynamics between genotypes was assessed in fura2-loaded LV myocytes, whereas I/R-injury was assessed ex vivo. Results: In both humans and mice, myocardial PKARIα disulfide formation was found to be significantly increased (2-fold in humans, P =0.023; 2.4-fold in mice, P <0.001) in response to I/R in vivo. In mouse LV cardiomyocytes, disulfide-containing PKARIα was not found to impact catalytic activity, but instead led to enhanced AKAP (A-kinase anchoring protein) binding with preferential localization of the holoenzyme to the lysosome. Redox-dependent regulation of lysosomal two-pore channels by PKARIα was sufficient to prevent global calcium release from the sarcoplasmic reticulum in LV myocytes, without affecting intrinsic ryanodine receptor leak or phosphorylation. Absence of I/R-induced PKARIα disulfide formation in "redox dead" knock-in mouse hearts resulted in larger infarcts (2-fold, P <0.001) and a concomitant reduction in LV contractile recovery (1.6-fold, P <0.001), which was prevented by administering the lysosomal two-pore channel inhibitor Ned-19 at the time of reperfusion. Conclusions: Disulfide modification targets PKARIα to the lysosome, where it acts as a gatekeeper for two-pore channel–mediated triggering of global calcium release. In the postischemic heart, this regulatory mechanism is critical for protection from extensive injury and offers a novel target for the design of cardioprotective therapeutics. Abstract : Supplemental Digital Content is available in the text.